2011
DOI: 10.1007/s13149-011-0157-1
|View full text |Cite
|
Sign up to set email alerts
|

Étude de la part du paludisme chez les consultants fébriles et des indices plasmodiques chez des écoliers dans la région du Trarza, République islamique de Mauritanie

Abstract: A study was performed to appreciate the importance of malaria in the low valley of the Senegal River North Bank in Mauritania. The malaria incidence was assessed among patients visiting the regional hospital of Rosso (Trarza region) for a "presumptive malaria", a diagnosis assigned by the clinicians based on fever and other suggestive symptoms of malaria. The malaria prevalence rate was also measured in schoolchildren. A total of 1431 febrile outpatients were sampled for thick and thin blood films, between Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…15,16 The screening prevalence for malaria in the 37 studies that tested for this aetiology ranged from 0% in Angola in 2009 to 79.1% in Tanzania in 2013. 17,18 Of note, in those studies where both health workers and expert researchers performed diagnostic tests, or test results were PCR confirmed, positivity rates for blood slides judged by health workers were consistently higher than those judged by research experts or PCR rates (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…15,16 The screening prevalence for malaria in the 37 studies that tested for this aetiology ranged from 0% in Angola in 2009 to 79.1% in Tanzania in 2013. 17,18 Of note, in those studies where both health workers and expert researchers performed diagnostic tests, or test results were PCR confirmed, positivity rates for blood slides judged by health workers were consistently higher than those judged by research experts or PCR rates (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Malaria prevalence was also shown to be low in Rosso (16°30’N, 15°48’W), a city situated along the Senegal River, and its surrounding villages, in 2004–2006 [ 19 ]. In that study, 36 of 1431 (2.5 %) febrile paediatric and adult patients had positive smears, mostly due to P. falciparum , and 9 of 1040 (0.9 %) asymptomatic schoolchildren were malaria parasite carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Also the European Environment Agency [87], the European Parliament [88], and two recent papers [89,90] have expressed preoccupations about the effects on human health, particularly on that of young people, by the continuous RF exposure produced in public places and at home by wi-fi for internet access and MP use. The European Parliament has also pointed at "the need to evaluate scientific integrity of the authors, in order to forestall possible risks, conflicts of interest or even frauds which tend to arise in a context of growing competition among researchers" [88].…”
Section: Discussionmentioning
confidence: 99%